Pengaruh Pemberian Jus Mentimun Mix Air Kelapa Muda Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi di Posbindu Srikndi Rt.004/Rw.07 Kelurahan Lenteng Agung Tahun 2023 - Julien A.Nifmaskossu; Risky Kusuma Hartono; Bambang Suryadi (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
With an unhealthy lifestyle such as having a smoking habit, irregular and unhealthy eating patterns will have an impact on hypertension or high blood pressure, which later on from the bad habits above will have further impacts, namely complications of heart disease, heart failure, stroke. , and damage to the kidneys. Problems that can cause an increase in blood pressure can be controlled or prevented by using cucumber and young coconut water.To determine the effect of giving cucumber juice mixed with young coconut water on reducing blood pressure in hypertensive patients. This type of research is in the form of an experiment with a Pre Test and Post Test With Control Group Design research design. The sample in this study was 50 respondents who were divided into two groups, namely 25 samples of treatment group respondents who were given 200 grams of cucumber juice mixed with young coconut water and 25 samples of control group respondents who were not given treatment. The statistical test used to determine the effect uses the T-test. The results of this study indicate that there was an influence on blood pressure in the treatment group given cucumber juice mixed with young coconut water in hypertension sufferers, namely that the results of statistical tests obtained an average value of pre-systolic blood pressure of 161.12 mmHg and an average value of post-systolic blood pressure. systolic blood pressure was 128.48 mmHg and the average value of pre-diastolic blood pressure was 91.16 mmHg and the average value of post-diastolic blood pressure was 80.00 mmHg. A p-value of 0.000 (< 0.05) for systolic blood pressure obtained a p-value of 0.000 (< 0.05) and diastolic blood pressure obtained a p-value of 0.000 (< 0.05). Due to the benefits of cucumber and young coconut water which are beneficial for lowering blood pressure. There is an effect of giving cucumber juice mixed with young coconut water on changes in systolic and diastolic blood pressure in the treatment group and can reduce blood pressure in patients suffering from hypertension aged 40 - 70 years at Posbindu Srikandi RT.004/RW.07 Kel. Lenteng Agung.